Ecotheology as a New Direction in the Politics and Policy of Islamic Religious Education in Indonesia - Dian Febrianingsih; Ahmad Arifi; Sabarudin Sabarudin (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study aims to analyze ecotheology as a new direction in the politics and policy of Islamic religious education in Indonesia, particularly in responding to contemporary ecological challenges. This research employs a qualitative approach using library research. Data sources consist of policy documents issued by the Ministry of Religious Affairs, theoretical works on ecotheology, and scholarly articles and books related to Islamic education and ecological studies. Data were collected through a document review and a systematic literature review, focusing on themes of relevance. The data were analyzed using content analysis, which involved data reduction, thematic categorization, and drawing interpretative conclusions. The findings reveal that the integration of ecotheology has begun to appear in national educational policy, as reflected in programs such as Green Theology, forest endowment initiatives, and large-scale tree-planting movements. Challenges persist in the dominance of normative curricula and the limited capacity of educators. Yet, significant opportunities emerge through the roles of pesantren, religious leaders, and faith-based organizations as agents of ecological change. Theoretically, this study expands the discourse on Islamic education by positioning ecotheology as an ethical and political framework for understanding. Practically, the findings guide policymakers and Islamic educational institutions in designing more ecological, transformative, and sustainable learning policies and programs.